Теорія суспільного вибору: компетенція політичного та економічного механізмів в системі трудових можливостей суспільства - Мороз, Володимир Михайлович (Національний університет цивільного захисту України, 2018)
Визначено особливості функціонування системи трудових відносин в контексті змісту основних принципів теорії суспільного вибору; розглянуто компетенцію політичного та економічного механізмів у регулюванні розвитку системи трудового потенціалу суспільства; обґрунтовано втрати суспільства від неповного використання трудового потенціалу його представників; сформульовано висновки щодо можливості використання політичного та економічного механізмів в системі державного управління розвитком трудових можливостей суспільства.

The peculiarities of functioning of the system of labor relations in the context of content of main principles of the theory of public choice were defined; the competence of political and economic mechanisms in regulation of development of the system of labor potential of society was reviewed; the society’s losses from incomplete usage of labour potential of its representatives of substantiated; the conclusions as for possibilities of us-ing political and economic mechanisms in the system of public administration of labour possibilities of society were formed.
The theory of social choice: the competence of political and economic mechanisms in the system of labor opportunities of society
Keywords: ринкова система; управлінські рішення; трудовий потенціал суспільства; об`єкти державного управління; суб`єкти державного управління; theory of public choice; social choice; political system; management decisions; society`s losses; objects of public administration; economic mechanisms; labour potential of society; market system